Non-pharmacological treatment for depressed older patients in primary care: A systematic review and meta-analysis. - Floor Holvast; Btissame Massoudi; Richard C Oude Voshaar; Peter F M Verhaak (PLoS ONE, 2017)
Background Late-life depression is most often treated in primary care, and it usually coincides with chronic somatic diseases. Given that antidepressants contribute to polypharmacy in these patients, and potentially to interactions with other drugs, non-pharmacological treatments are essential. In this systematic review and meta-analysis, we aimed to present an overview of the non-pharmacological treatments available in primary care for late-life depression. Method The databases of PubMed, PsychINFO, and the Cochrane Central Register of Controlled Trials were systematically searched in January 2017 with combinations of MeSH-terms and free text words for "general practice," "older adults," "depression," and "non-pharmacological treatment". All studies with empirical data concerning adults aged 60 years or older were included, and the results were stratified by primary care, and community setting. We narratively reviewed the results and performed a meta-analysis on cognitive behavioral therapy in the primary care setting. Results We included 11 studies conducted in primary care, which covered the following five treatment modalities: cognitive behavioral therapy, exercise, problem-solving therapy, behavioral activation, and bright-light therapy. Overall, the meta-analysis showed a small effect for cognitive behavioral therapy, with one study also showing that bright-light therapy was effective. Another 18 studies, which evaluated potential non-pharmacological interventions in the community suitable for implementation, indicated that bibliotherapy, life-review, problem-solving therapy, and cognitive behavioral therapy were effective at short-term follow-up. Discussion We conclude that the effects of several treatments are promising, but need to be replicated before they can be implemented more widely in primary care. Although more treatment modalities were effective in a community setting, more research is needed to investigate whether these treatments are also applicable in primary care. Trial registration PROSPERO CRD42016038442.